Content and Fatty Acid Composition of Neutral Acylglycerols in Euonymus Fruits. (13th February 2014) - Sidorov, Roman A.; Zhukov, Anatoly V.; Pchelkin, Vasily P.; Vereshchagin, Andrei G.; Tsydendambaev, Vladimir D.
Abstract: The content and fatty acid (FA) composition of FA neutral acylglycerols (NAG), a mixture of 1, 2, 3‐triacyl‐ sn ‐glycerols (TAG) and 3‐acetyl‐1, 2‐diacyl‐ sn ‐glycerols ( ac DAG), were determined in the seeds and arils of fruits of 14 Euonymus L. species. On the average, the seeds exceeded the arils in the absolute and relative dry matter content 2.9‐ and 1.9‐fold, respectively, and separate plant species greatly differed in NAG composition. The proportions of TAG in the NAG of seeds and arils were 4–5 and ~98 %, respectively. The degree of FA unsaturation in aril NAG was higher than in the seed NAG, and in ac DAG—higher, than in TAG. In the NAG, 14 major FA molecular species (excluding minor FA) were found, and linoleic, oleic, palmitic, and linolenic acids were predominant. NAG of separate taxonomic units of the genus Euonymus L. differed from each other in the concentration of major FA as well as other FA. So, by using statistical analysis, it was definitely established that the species from the subgenus Euonymus were characterized by an increased content of linoleic acid, while those from the subgenus Kalonymus, by the predominance of oleic acid. Meanwhile, the species of the section Euonymus were marked by an enhanced concentration of a number of hexa‐ and octadecenoic FA positional isomers.